2021
DOI: 10.5230/jgc.2021.21.e11
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Observation of Gastric Adenocarcinoma of Fundic Gland Mucosa Type before and after Helicobacter pylori Eradication: a Case Report

Abstract: Gastric adenocarcinoma of the fundic gland mucosa type (GA-FGM) was proposed as a new variant of gastric adenocarcinoma of the fundic gland type (GA-FG). However, at present, the influence of Helicobacter pylori and the speed of progression and degree of malignancy in GA-FGM remain unclear. Herein, we report the first case of intramucosal GA-FGM that was endoscopically observed before and after H. pylori eradication over 15 years. The lesion showed the same tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…19 However, GA-FGs were reported to follow a relatively benign course and seemed to have a favorable prognosis. [20][21][22] Thus, some reports on GA-FGs preferred the term of "oxyntic gland adenoma (OGA)" or "chief cell-predominant gastric polyps"; they regarded OGA as an intramucosal phase of GA-FGs. 23 Some have suggested that this may represent "prolapse-type" misplaced glands rather than true submucosal invasion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 However, GA-FGs were reported to follow a relatively benign course and seemed to have a favorable prognosis. [20][21][22] Thus, some reports on GA-FGs preferred the term of "oxyntic gland adenoma (OGA)" or "chief cell-predominant gastric polyps"; they regarded OGA as an intramucosal phase of GA-FGs. 23 Some have suggested that this may represent "prolapse-type" misplaced glands rather than true submucosal invasion.…”
Section: Resultsmentioning
confidence: 99%
“…In the conventional evaluation of GA, submucosal invasion is regarded as a significant risk factor associated with lymph node metastasis 19 . However, GA‐FGs were reported to follow a relatively benign course and seemed to have a favorable prognosis 20–22 . Thus, some reports on GA‐FGs preferred the term of “oxyntic gland adenoma (OGA)” or “chief cell‐predominant gastric polyps”; they regarded OGA as an intramucosal phase of GA‐FGs 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 47 cases of GA‐FGM (47 lesions) have been reported in the literature, and the clinicopathological characteristics are summarized in Table 4. The deeper parts of the lesions covered with atypical foveolar epithelium showed complicated glands consisting of tumor cells with prominent atypia and were immunohistochemically positive for MUC5AC 6,34–40 . The average size of GA‐FGM was mostly >15 mm, and three lesions reported by Ushiku et al 6 .…”
Section: Histopathological Findingsmentioning
confidence: 96%
“…This has led to uncertainty concerning the real-world frequency of OGNs (8), as previous reports have described the prevalence at less than 1/10,000 (<0.01%). Furthermore, the relationship with H. pylori infection, association with oral proton pump inhibitor (PPI) use, frequency of submucosal invasion, and rate of lymph node metastasis have not yet been clarified (8,11,12,(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%